Modificação na parede celular e nas enzimas oxidativas durante a maturação de frutos de goiabeira "Paluma" submetidas à adubação potássica - Silva, Aline Priscilla Gomes da (2014)
As an essential element for plant metabolism, potassium has important role as an activator or as cofactor of many enzymes, acting in several metabolic processes. The supply of potassium (K) fertilization can induce several processes, including those related to fruit quality. Thus, K is known as the "quality element". Therefore, it was evaluated the Paluma guava cultivar, subjected to three doses of K in three maturity stages, with the objective of determining its influency on the contents of total and soluble pectins, percentage of pectin s solubilization, the activity of the enzymes of the cell wall and oxidative metabolism. Three doses of K per plants were applied: 50 g de K2O; 100 g de K2O e 150 g de K2O, fixing the doses of N and P of 150 g and 140 g per plant, respectively. The evaluations were performed in the endocarp of the fruits. The classification of the three maturity stages was established according to the skin color. The variables evaluated were: total pectin (TP), soluble pectin (SP), insoluble pectin (IP), and percentage of solubilization of pectic substances (% Sol), activity of the enzymes pectin methylesterase (PME), polygalacturonase (PG), polyphenoloxidase (PPO), peroxidase (POD). The experimental design was the completely randomized in a 3 x 3 factorial scheme (doses of K x maturity stage), with the replication of three plants and 36 fruits from each plant. The dose of 100 g K plant-1 resulted in higher values of TP, IP, lower activities of PME, PG, and lowed activities of oxidative enzymes for both PPO and POD, reflecting on the greater stability of the cell wall and possibly on longer postharvest life of the fruit.